The benefits of cashless payment transaction among the students of Kolej Universiti Islam Perlis - Nur Syaza, Shafie (2023)
Malaysia's development in cashless payment consumption shows a good performance and is growing rapidly since recently. After the phase of the COVID-19 pandemic, the use of cashless payment is increasing and to some extent it is providing benefits to users. However, there are some specific studies done on the benefits of cashless payments. The purpose of choosing this study is to show the benefits that influence consumers to use cashless payments. Three independent variables were used in this study to investigate the benefits of cashless payments transaction including perceived usefulness, perceived ease of use and perceived security. 1300 sets of survey questions were randomly distributed to students of Kolej Universiti Islam Perlis (KUIPs) and only 297 were returned. The data obtained was analyzed using Pearson's correlation and Multiple Regression. The results of the study show that the independent variable is positively correlated with the benefits of cashless payment transactions except one independent variable which is perceived security. This study is considered a very useful finding for future researchers.